N′-[(1E)-(4-Fluorophenyl)methylidene]adamantane-1-carbohydrazide, C18H21FN2O - Al-Wahaibi, Lamya H.; Abdelbaky, Mohammed S. M.; Garcia-Granda, Santiago; Reiss, Guido J.; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter Open, 2023)
C18H21FN2O, triclinic, P 1 ‾ (no. 2), a = 10.6377(5) Å, b = 14.4869(7) Å, c = 21.0557(13) Å, α = 98.583(5)°, β = 91.979(4)°, γ = 90.101(4)°, V = 3206.5(3) Å3, Z = 8, Rgt(F) = 0.0815, wRref(F2) = 0.1930, T = 172 K.